FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KETERSEDIAAN TEMPAT PENYIMPANAN DAN PENGELOLAAN VAKSIN IMUNISASI DASAR PADA ANAK - Dwi Astuti; Atun Wigati; Yayuk Mundriyastutik (Universitas Muhammadiyah Kudus, 2023)
Vaccines are biological elements that have certain characteristics and require handling of the vaccine chain since they are specially produced in the factory until they are used in health units. The purpose of this study was to determine the factors related to the availability of storage and management of basic vaccines in children at the Pukesmas Gondosari Kudus. This type of research uses descriptive research with a cross sectional approach with a total of 20 respondents. Sampling with total sampling technique. This study using the chi square test shows that there are factors related to the factors of health workers with the availability of places and management of basic vaccines at the Puskesmas Gondosari Kudus. The chi square test obtained a p value of 0.001 (ɑ 0.05) Ho was rejected. There are factors that relate to facilities and infrastructure with the availability of places and management of basic vaccines at the Puskesmas Gondosari Kudus. The chi square test obtained a p value of 0.006 (ɑ 0.05) Ho was rejected. Conclusion: There are factors related to the availability of storage and management of basic vaccines at Puskesmas Gondosari Kudus.